2013
DOI: 10.1186/2050-6511-14-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early life exposure to ultraviolet C radiation on mitochondrial DNA content, transcription, ATP production, and oxygen consumption in developing Caenorhabditis elegans

Abstract: BackgroundMitochondrial DNA (mtDNA) is present in multiple copies per cell and undergoes dramatic amplification during development. The impacts of mtDNA damage incurred early in development are not well understood, especially in the case of types of mtDNA damage that are irreparable, such as ultraviolet C radiation (UVC)-induced photodimers.MethodsWe exposed first larval stage nematodes to UVC using a protocol that results in accumulated mtDNA damage but permits nuclear DNA (nDNA) repair. We then measured the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 62 publications
2
66
0
Order By: Relevance
“…Interestingly, the same has been reported for low levels of some mitotoxicants, such as arsenic (Schmeisser et al 2013); however, we recently found that concentrations of arsenic that were harmless or even beneficial in wild-type Caenorhabditis elegans were instead toxic to fusion-deficient individuals (Luz et al 2017). On the other hand, some mitochondrial perturbations can have persistent, deleterious consequences (Berthiaume and Wallace 2007a, b; Chan et al 2007; Ditzel et al 2015; Divi et al 2010; Leung et al 2013; Saben et al 2016; Wood et al 2015), and thus may contribute the developmental origins of adult health and disease. Testing this possibility will be an additional, important future direction, especially given the very different mitochondrial morphologies and functions observed in early-stage organisms and undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same has been reported for low levels of some mitotoxicants, such as arsenic (Schmeisser et al 2013); however, we recently found that concentrations of arsenic that were harmless or even beneficial in wild-type Caenorhabditis elegans were instead toxic to fusion-deficient individuals (Luz et al 2017). On the other hand, some mitochondrial perturbations can have persistent, deleterious consequences (Berthiaume and Wallace 2007a, b; Chan et al 2007; Ditzel et al 2015; Divi et al 2010; Leung et al 2013; Saben et al 2016; Wood et al 2015), and thus may contribute the developmental origins of adult health and disease. Testing this possibility will be an additional, important future direction, especially given the very different mitochondrial morphologies and functions observed in early-stage organisms and undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out experiments in the nematode Caenorhabditis elegans to test the effect of persistent mtDNA damage, using a protocol that resulted in the accumulation of high levels of mtDNA photoproducts while allowing for the repair of most of the simultaneously induced nDNA damage (39, 40). This damage was generated by UV exposure in the first of the four larval stages of the organism.…”
Section: Effect Of Dna Damaging Agents On Mtdnamentioning
confidence: 99%
“…This damage was generated by UV exposure in the first of the four larval stages of the organism. The irradiation resulted in lower levels of mtDNA (i.e., lower mtDNA copy number per cell), lower levels of ATP, lower levels of oxygen consumption, and dose-responsive inhibition of larval development (39, 40). The mRNA levels for mtDNA-encoded proteins were initially lower than in unexposed nematodes, but later rebounded (40).…”
Section: Effect Of Dna Damaging Agents On Mtdnamentioning
confidence: 99%
“…They are essentially the power house of the cell by producing ATP as a driving fuel for the cells [11]. Interestingly, the mitochondria are the focal point for idiopathic diseases and genetic diseases due to their sensitivity to environmental insult.…”
Section: Introductionmentioning
confidence: 99%